0303 Neurobiological Basis of Sleep Disturbances in Tauopathies: Human Wake-Promoting Neurons Degenerate More in Alzheimer's Disease. (12th April 2019) - Oh, Jun; Eser, Rana A; Ehrenberg, Alexander J; Morales, Dulce; Petersen, Cathrine; Theofilas, Panos; Resende, Elisa; Cosme, Celica; Seeley, William W; Spina, Salvatore; Walsh, Christine M; Neylan, Thomas C; et al.
Abstract: Introduction: Alzheimer's disease (AD) and the four-repeat tauopathies, corticobasal degeneration (CBD) and progressive supranuclear palsy (PSP), are neurodegenerative diseases associated with accumulation of abnormal tau protein. Despite exhibiting different patterns of sleep dysfunction, AD, CBD, and PSP all feature pathological accumulation of tau in brainstem and hypothalamic nuclei regulating sleep-wake behavior. Given that the clinical pattern of sleep-wake disturbances shows prominent daytime sleepiness in AD but decreased sleep drive in PSP, we hypothesized that wake-promoting neurons (WPNs) are more vulnerable to the toxic effects of AD-tau than to CBD-tau or PSP-tau. Methods: Double-label immunohistochemistry and unbiased stereology were performed on noradrenergic locus coeruleus (LC), orexinergic lateral hypothalamic area (LHA), and histaminergic tuberomammillary nucleus (TMN) in 34 well-characterized human postmortem brains (13 AD, 7 CBD, 7 PSP, 7 Controls) to quantify tau neuronal burden, neuronal loss, and neuronal ability to synthesize neurotransmitters (TH+, orexin+, or HDC+). Results: All regions of interest exhibited a significant tau burden in all pathological cases. Compared to Controls, AD cases exhibited a reduction of 76.08% LC, 71.80% LHA, and 62.06% TMN neurons. In AD, we found a similar pattern of reduction when considering only neurotransmitter-positive neurons. Neuronal loss in LC in CBD and PSP was significant but milder than in AD. We failed to detect neuronal loss in LHA and TMN of PSP and CBD cases, despite a high tau burden. Finally, we found a significantly lower proportion of neurotransmitter-synthesizing neurons in all three conditions, suggesting that tau deposits lead to an impaired neuronal ability to transmit signals. Conclusion: Our results support our hypothesis that WPN are particularly vulnerable to AD-tau. This severe degeneration of the arousal system in AD may partially explain increases in daytime napping. Further studies should examine if the severe sleep deprivation without a propensity for daytime somnolence in PSP can be explained by a disproportional degeneration of sleep-promoting neurons compared to WPNs. Understanding the neurobiological basis of the differences in sleep-wake disturbances in tauopathies is crucial for developing targeted interventions. Support (If Any): Tau Consortium, NIH